2007
DOI: 10.1111/j.1365-294x.2007.03612.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in symbiont distribution between closely related coral species over large depth ranges

Abstract: Symbiotic algae in coral species distributed over a large depth range are confronted with major differences in light conditions. We studied the genetic variation of Symbiodinium in the coral genus Madracis over depth (5-40 m) and at two different colony surface positions. Using polymerase chain reaction-denaturing gradient gel electrophoresis ITS2 nuclear ribosomal DNA analyses, we consistently identified three symbiont genotypes with distributions that reveal patterns of host specificity and depth-based zonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
154
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(158 citation statements)
references
References 74 publications
1
154
1
Order By: Relevance
“…Symbiont abundances (per coral surface area), higher in M. meandrites than in the other two species, are known to be a species-specific trait and probably related to threedimensional space availability within the coral tissue [8] and to the genetically constrained cell size of particular symbiont lineages. [52] Although Symbiodinium numbers inside the coral tissue are known to vary over time and space for individual species, [36,53] neither time of the day nor depth explained their variation in the current study. Approximately 60 % of the variation in DMSP concentration per unit area was, according to our multiple linear regression models, explained by symbiont abundance within the tissue (see Fig.…”
Section: Dmsp Concentration In Coral Tissue and De Novo Productionmentioning
confidence: 90%
See 2 more Smart Citations
“…Symbiont abundances (per coral surface area), higher in M. meandrites than in the other two species, are known to be a species-specific trait and probably related to threedimensional space availability within the coral tissue [8] and to the genetically constrained cell size of particular symbiont lineages. [52] Although Symbiodinium numbers inside the coral tissue are known to vary over time and space for individual species, [36,53] neither time of the day nor depth explained their variation in the current study. Approximately 60 % of the variation in DMSP concentration per unit area was, according to our multiple linear regression models, explained by symbiont abundance within the tissue (see Fig.…”
Section: Dmsp Concentration In Coral Tissue and De Novo Productionmentioning
confidence: 90%
“…An example of such a mechanism is the photoprotective regulation of the light environment within the coral tissue provided by tissue-associated fluorescent pigments. [57] Although we cannot exclude that the range of light irradiance in the current study was too narrow to cause significantly different levels of DMSP, colonies collected at 5 m experience far higher photosynthetic radiation (PAR) than at 25 m: ,1000 mmol photons m À2 s À1 of downwelling irradiance at 5 m v. 250 mmol photons m À2 s À1 at 25 m. [36] In the study of Hill et al, [35] focussing on the photoprotective role of betaines (quaternary ammonium metabolites) in corals, DMSP was also included because of its related chemical structure (a tertiary sulfonium compound). Consistent with our results, Hill et al [35] found that DMSP concentrations of members of the genus Madracis did not vary significantly with irradiance exposure (after comparisons between different depths, between shaded and exposed colonies and between different times of the day).…”
Section: Dmsp Concentration In Coral Tissue and De Novo Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symbionts acclimatised to high irradiances are characterised by high PS max and E k , with low a, but the opposite occurs for symbionts acclimatised to low-irradiance as the symbionts attempt to optimise their light capture and utilisation capability (Anthony and Hoegh-Guldberg 2003;Cooper and Ulstrup 2009). However, these parameters are influenced by variation in seawater temperature (Coles and Jokiel 1977;Warner et al 1996;Fitt et al 2001), flow regime (Nakamura et al 2005), diurnal changes in benthic irradiance (Jones and Hoegh-Guldberg 2001;Lesser and Gorbunov 2001) and symbiont genotype (Frade et al 2008;Hennige et al 2009). Thus, these factors must be accounted for when using symbiont photophysiology to infer changes in water quality.…”
Section: Symbiont Photophysiologymentioning
confidence: 99%
“…Phylogenies such as those based on nuclear ribosomal deoxyribonucleic acid (rDNA) divide the genus into several large clades (Rowan and Powers 1991). The internal transcribed spacer regions 1 and 2 (ITS1 and ITS2) further characterize numerous subcladal genetically distinct types (Lajeunesse 2001;van Oppen et al 2001), which closely approximate physiologically and ecologically distinct populations (Lajeunesse 2002;Warner et al 2006;Frade et al 2008).…”
mentioning
confidence: 99%